y2=-x2-8x+6
Oh, dude, isolating y2 in an equation just means getting y2 by itself on one side. It's like setting it free from the other numbers, giving it some space to breathe. So, you'd probably end up with something like y2 = (other stuff), and y2 would be like, "Finally, I can be me without all these other numbers holding me back."
The formula: distance=sqrt(((x1-x2)*(x1-x2))+((y1-y2)*(y1-y2))+((z1-z2)*(z1-z2))) In DarkBASIC it's: function distance3D(x1,y1,z1,x2,y2,z2) x=x1-x2 y=y1-y2 z=z1-z2 result=sqrt((x*x)+(y*y)+(z*z)) endfunction result In classic BASIC I think it's: FUNCTION distance3D(x1,y1,z1,x2,y2,z2) x=x1-x2 y=y1-y2 z=z1-z2 result=SQRT((x*x)+(y*y)+(z*z)) RETURN result END FUNCTION
The inner circle is x2 + y2 = 4. The radius of the inner circle is the square root of 4, which is 2. To find the radius of the outer circle, multiply 2 times 4. The radius of the outer circle is 8. Square 8 (82 or 8 x 8) to find the number to put into the equation of the outer circle. This is 64. The equation for the outer circle is x2 + y2 = 64.
There is no expansion for x2 + y2
y2=-x2-8x+6
Oh, dude, isolating y2 in an equation just means getting y2 by itself on one side. It's like setting it free from the other numbers, giving it some space to breathe. So, you'd probably end up with something like y2 = (other stuff), and y2 would be like, "Finally, I can be me without all these other numbers holding me back."
y2 - 64 can be written as y2 - 82, which is of the form of a2 - b2.And a2 - b2 is factored as (a-b)(a+b).Therefore, y2 - 64 is factored as (y+8)(y-8).
The equation of a circle centered at the origin is x2 + y2 = r2; in this case, x2 + y2 = 64.The equation of a circle centered at the origin is x2 + y2 = r2; in this case, x2 + y2 = 64.The equation of a circle centered at the origin is x2 + y2 = r2; in this case, x2 + y2 = 64.The equation of a circle centered at the origin is x2 + y2 = r2; in this case, x2 + y2 = 64.
If y=8, then 8 squared is 64.
y2 - 16y + 64 = 0 (y - 8)2 = 0 y - 8 = 0 y = 8
8
4 - y2 can be written as 22 - y2. This has become of the form of x2 - y2.Expansion for x2 - y2 is (x+y)(x-y).So, 4 - y2 = 22 - y2 = (2+y)(2-y)
8
88 + 5y - y2 66 - 3y + y2 Subtract: 22 + 8y -2y2
(y2+13y+22)/(y+2) = (y+11)
x2 + y2 = 64